Faktor- Faktor Yang Mempengaruhi Purchase decision Konsumen pada UMKM di Belitung - Patria Gantara; Ida Bagus Nyoman Udayana; Lusia Tria Hatmanti Utami (Jurnal Bisnis, Manajemen, dan Ekonomi, 2023)
This study aims to determine analyzing the effect Factors Influencing Consumer Purchase Decisions on MSMEs in Belitung such as of Corporate Social Responsibility (CSR), social media marketing, store environment and perceived value. The population to be studied is all SMEs in Belitung and the sample in this study is 110 respondents from all SMEs in Belitung with data collection techniques using a questionnaire. various tests carried out such as validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, hypothesis testing through T and F tests, and the coefficient of determination test was carried out. The results of the study found that Corporate Social Responsibility, Social Media Marketing, Store Environment and Perceived Value had a positive and significant effect on Purchase Decisions for SMEs in Belitung. This means that the better the Social media marketing.